PERAN PERENCANAAN SUMBER DAYA MANUSIA DALAM ANALISIS PEKERJAAN DAN REKRUTMEN - Roy Qurrotu Ainin; Mhd. Irsan Nasution; Tri Pangkat Soesiawan; M. Alkaf; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Human resource planning in the industrial revolution of the society 5.0 era must be carried out carefully, strategically and effectively in responding to the challenges of human resources that have flexibility that changes very quickly. The purpose of this research is to provide an explanation of the study of the role of human resource planning in job analysis and recruitment of human resources within the company, namely by formulating human resource planning steps based on job analysis and explaining the importance of job analysis in developing recruitment and workforce development strategies, and evaluating human resource planning effectively and efficiently by making continuous improvements to the human resource planning that has been arranged in accordance with the vision and mission of the Company. The research method used is descriptive analytical method obtained from secondary data sources taken from journals, articles and books using a qualitative research approach to literature study. The results of this study indicate that HR planning based on job analysis can provide a strategic advantage in managing the workforce in the company so that human resource planning in this study has an important role in job analysis and job analysis provides a strong basis for developing HR strategies, from recruitment to company development